Demand-Based Inventory Management Of Menstrual ProductsFor Sustainability And Health - PARKAVI MADURAIPANDIYAN; KALAIARASI KALAICHELVAN (The Scientific Temper, 2026)
This study looks at how to manage menstrual product stock for 100 people over threeyears. Monthly demand was collected and analyzed using Heptagonal NeutrosophicFuzzy Numbers (HNFN) to handle uncertainty in how much people need. The fuzzynumbers were turned into a single clear demand number using defuzzification. Then,the Economic Order Quantity (EOQ) was calculated for three real-life scenarios. Wealso made 3D plots to show how EOQ changes when demand and setup costs change.The study supports SDG 3 Good Health, SDG 5 Gender Equality, and SDG 12Responsible Consumption by helping organizations provide the right amount ofproducts, avoid shortages, and reduce waste. This method can guide better planningfor menstrual products in schools, hospitals, or communities.